2016
DOI: 10.1523/jneurosci.4597-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotrophic Factor Receptor p75 in the Rat Dorsolateral Striatum Drives Excessive Alcohol Drinking

Abstract: Brain-derived neurotrophic factor (BDNF) signaling in the dorsolateral striatum (DLS) keeps alcohol intake in moderation. For example, activation of the BDNF receptor tropomyosin receptor kinase B (TrkB) in the DLS reduces intake in rats that consume moderate amounts of alcohol. Here, we tested whether long-term excessive consumption of alcohol produces neuroadaptations in BDNF signaling in the rat DLS. We found that BDNF was no longer able to gate alcohol self-administration after a history of repeated cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 70 publications
4
46
1
Order By: Relevance
“…Here, we used inbred alcohol‐preferring iP rats to assess whether alcohol‐seeking behavior can be modulated via epigenetic transmission through the male germline. In this experiment, rats voluntarily consumed relatively high quantities of alcohol, we observed consumption of 1 g/kg/20 min session on average, which is similar to binge drinking patterns seen in humans . Thus, our finding suggests that this level of alcohol use is not sufficient to influence alcohol consumption in offspring.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Here, we used inbred alcohol‐preferring iP rats to assess whether alcohol‐seeking behavior can be modulated via epigenetic transmission through the male germline. In this experiment, rats voluntarily consumed relatively high quantities of alcohol, we observed consumption of 1 g/kg/20 min session on average, which is similar to binge drinking patterns seen in humans . Thus, our finding suggests that this level of alcohol use is not sufficient to influence alcohol consumption in offspring.…”
Section: Discussionsupporting
confidence: 69%
“…In this experiment, rats voluntarily consumed relatively high quantities of alcohol, we observed consumption of 1 g/kg/20 min session on average, which is similar to binge drinking patterns seen in humans. 25,26 Thus, our finding suggests that this level of alcohol use is not sufficient to influence alcohol consumption in offspring.…”
Section: Effect Of Paternal Alcohol Exposure On Voluntary Alcohol Cmentioning
confidence: 66%
“…p75NTR can also prolong cell-surface TrkA-dependent signaling ( Makkerh et al, 2005 ), thereby enhancing TrkA signaling capacity ( Verdi et al, 1994 ; Epa et al, 2004 ). Interestingly, knockdown of p75NTR expression significantly reduced excessive alcohol intake in rats ( Darcq et al, 2016 ), whereas our own findings suggest that increased p75NTR might be involved in suppressing METH-seeking behavior, since the SS rats also show less cue-induced drug seeking ( Torres et al, 2017 ). This statement hints to the possibility that SS rats might have a better ability to learn and establish memory for adverse events through the activation of the NGF signaling cascade.…”
Section: Discussioncontrasting
confidence: 57%
“…The IAE model is usually not used as a model of EtOH dependence because of the relatively low blood EtOH levels that are achieved and low, or lack of, somatic or emotional signs of withdrawal (Cippitelli et al., ; George et al., ). However, some research groups have observed significant withdrawal symptoms (Fu et al., ; Steensland et al., ) and evidence of compulsive‐like drinking (Carnicella et al., ; Darcq et al., ; Depoy et al., ; Hopf and Lesscher, ; Seif et al., ) in the IAE model that may be relevant to AUDs. The present study confirmed the relevance of the IAE model to AUD by demonstrating that a history of moderate but prolonged (5 months) IAE in young adult rats accelerates the escalation of EtOH drinking and produces compulsive‐like drinking when rats maintain blood EtOH levels that are >150 mg/100 ml.…”
Section: Discussionmentioning
confidence: 99%